ANALISIS PROSES MANAJEMEN JURNAL STUDI ILMU-ILMU AL-QUR'AN DAN TAFSIR DALAM UPAYA BENCHMARKING DAN PENGEMBANGAN SEBAGAI JURNAL ILMIAH TERAKREDITASI SCOPUS - Aida Hidayah (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2021)
This article discusses the efforts of strategic management in managing internationally accredited journals at UIN Sunan Kalijaga. The limited number of internationally accredited journals is still an unresolved problem, thus requiring support from stakeholders and internal journal management, such as strengthening human resources and manuscript quality. A qualitative method using benchmarking and strategic management approaches was used to evaluate the management of internationally accredited journals. Findings indicate that policy support from leadership and relevant stakeholders is needed to accommodate the needs for improving international journal accreditation. In addition, the management of journal management human resources should be enhanced through training and development. Therefore, strategic management elements should be implemented to increase the quantity of internationally accredited journals in the environment of UIN Sunan Kalijaga.